Conceptual design of an XML-driven, global XML FACT repository for XML document warehouses - Chang, Elizabeth; Rajugan, R.; Dillon, Tharam S. (IEEE Explore, 2005)
In this paper, we propose a view-driven, architectural construct for modelling and designing of a Global XML FACT (GxFACT) repository using logically grouped, geographically dispersed, XML document warehouses and Document Marts. To deal with organizations? evolving decision-making needs, we also provide three design strategies for building and managing of such GxFACT in the context of modelling further hierarchical dimensions and/or global document warehouses.